The government's role in legal protection of land ownership: Urutsewu case - Hariyanto, Hariyanto; Idamatussilmi, Idamatussilmi; Rismana, Daud (Legality : Jurnal Ilmiah Hukum, 2024)
Legal protection involves safeguarding human rights violated by others and ensuring the community fully exercises its legally granted rights. In Urutsewu, the conflict arose from the differing perceptions between the TNI and local farmers. The TNI uses the area for defence and weapons testing, while farmers use it to grow crops to support their families. Both parties claim land in Urutsewu for their reasons because there is no clarity on the ownership status between them. This study uses a socio-legal approach, analysing the intersection of law and society by considering social, cultural, and political factors that affect the functioning of the legal system, which aims to examine the government’s role in the protection of law and human rights and its efforts to resolve land ownership disputes in the coastal land area of Urutsewu Kebumen. Progress is being made in recognising legal protection and human rights for land rights ownership in Urutsewu, with land specifications now being clarified for both residents and the TNI. The land disputes stem from unclear land ownership (no certificate), prompting both parties to initiate land registration to ensure legal certainty and land protection in Urutsewu.